Typology and Peri-Urban Development of Yogyakarta City and Surrounding - ratika tulus; Bimastyaji Ramadan (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2021)
The emergence of peri-urban areas as a transition zone between villages and cities has been influenced by the increasing flow of urbanization. Peri-urban is a dynamically developing suburban area with a mix of rural and urban characteristics. This mixture of characters can be classified from land use patterns, demographic characteristics, economy, and availability of public infrastructure services. On the other hand, the impact of urbanization in urban areas provides positive things through economic growth that supports the sustainability of people in urban areas. The city of Yogyakarta is a growth center in the Special Region of Yogyakarta consisting of 14 sub-districts with significant operations in the trade and service sector. The rapid growth of the city of Yogyakarta has triggered the development of the surrounding area which is directly adjacent to several sub-districts in Sleman Regency. This study aims to examine the typology and development of Yogyakarta City and its surroundings in 2015-2019 with the research area being 20 sub-districts in Yogyakarta City and parts of Sleman Regency. The peri-urban zone typological study employs descriptive geographic analysis, overlays, and scoring. According to a series of analyses, there were developments and changes in the peri-urban typology in Yogyakarta area and its environs from 2015 to 2019, which were turned into urban areas in terms of physical, social, and economic factors.